Emerging Trends, Threats, and Opportunities in International Marketing: What Executives Need to Know - Czinkota, Michael R (Business Expert, 2012)
The context of international business has evolved over the years and has always refl ected the climate of the time. Three major changes that have taken place in the last decade or so should be noted. First, the landscape of the global economy changed drastically in the last decade or so. The Asian and Latin American fi nancial crises, the further expansion of the European Union (EU), and the emergence of BRIC (Brazil, Russia, India, and China) as economic powerhouses have occurred during this period. And most recently, the global fi nancial and economic crisis caused primarily by the U.S. subprime mortgage loan crisis since late 2008 is ravaging the integrity of the global economy with unprecedented severity. Second, the explosive growth of information technology tools, including the Internet and electronic commerce (e-commerce), has had a signifi cant effect on the way we do business internationally. On one hand, everyone seems to agree that business transactions will be faster and more global early on. And it is very true. As a result, the nature of the global supply chain and global trade as managed by multinational fi rms has fundamentally changed. However, on the other hand, the more deeply we have examined this issue, the more convinced we have become that certain things would not change or could even become more local as a result of globalization that the Internet and e-commerce bestow on us. Third, it is an underlying human tendency to desire to be different when there are economic and political forces of convergence (often referred to as globalization). When the globalization argument (and movement) became fashionable in the 1980s and 1990s, many of us believed that globalization would make global business easier. Doing business beyond national borders, indeed, has become easier, but this does not necessarily mean that customers want the same products in countries around the world. For example, many more peoples around the world than ever before are trying to emphasize cultural and ethnic differences as well as accepting those differences. Just think about many new countries being born as well as regional unifi cations taking place at the same time. Indeed, these global changes we have observed in recent years are more than extraordinary. As a result, business practitioners are facing enormous challenges to cope with those changes in an uncertain world. This book is constitutes a timely compilation of work addressing marketing in an uncertain world, competition from emerging and reemerging markets, global sourcing, and meeting old and new global challenges.